Hello there!
Answer: ⇒⇒ [tex]x=\frac{2}{e^3}[/tex]
___________________________________________________
Step-by-step explanation:
First you had to subtract by 6 from both sides of equation.
[tex]e^3x+6-6=8-6[/tex]
Simplify.
[tex]e^3x=2[/tex]
Then you divide by e³ from both sides of equation.
[tex]\frac{e^3x}{e^3}=\frac{2}{e^3}[/tex]
Simplify it should be the correct answer.
[tex]x=\frac{2}{e^3}[/tex]
____________________________________________________________
Hope this helps!
Thank you for posting your question at here on brainly.
Have a great day!
-Charlie